Job demands and turnover intention: Does work engagement mediate in the model ? - Zalfa Firyal Neparahman; Muhamad Ekhsan (Jurnal Mantik, 2023)
This study discusses the effect of Job Demands on Turnover Intention through Work Engagement on employees of one of the Hospitals in Cikarang. The purpose of this study was to test and analyze the effect of Job Demands on Turnover Intention through Work Engagement on employees of one of the Hospitals in Cikarang. The sampling technique uses probability sampling technique with a sample size of 72 respondents who are employees of one of the hospitals in Cikarang, which uses the Slovin formula. The analytical test tool used is SmartPLS 3.0 with the SEM (Structural Equation Modeling) analysis method. The results of this study indicate that Job Demands has an effect on Turnover Intention, Job Demands has no significant effect on Work Engagement, Work Engagement has no significant effect on Turnover Intention and Work Engagement is proven not to mediate the effect of Job Demands on Turnover Intention, it shows that Work Engagement has no impact on Turnover Intention caused by job demands at one of the Hospitals in Cikarang. Because the majority of employees have a positive assessment of the Work Engagement variable, it is therefore very important for companies to continue to maintain engagement with employees. Efforts that can be made include maintaining the relationship between superiors and employees to remain harmonious in order to reduce the level of employee turnover.